Magnitude of role-breadth self-efficacy in teacher proactive work behaviour - Peariasamy, Suguna Devi; Omar, Zoharah; Basri, Ramli; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2020)
Proactive behaviour at work (PWB) is aimed at bringing about change within the organization, such as by improving work methods, voicing ideas or concerns, and taking action to prevent problems from reoccurring (Strauss & Parker, 2014). PWB can add to organizational effectiveness (Axtell et al., 2000; Griffin et al., 2007; Rank, Pace, & Frese, 2004) and is especially important in school setting when teachers come into contact with students proactively and make them understand what is being taught clearly (Devonport, Biscomb, & Lane, 2010; Sheard & Carbone, 2008). Proactive behaviour in daily work is the quality that teachers must possess in order to make the education system more successful. Strauss (2015) highlighted that, in 21st century teaching and learning practices that emphasis flexibility, innovation and adaptation to changes. School organizations are rapidly looking for competencies and behaviours in teachers who can facilitate and adapt to new educational challenges. Teacher role-breadth self-efficacy (RBSE) is specifically important to meet the current demand in education and help teachers to prepare for future challenges. RBSE is more substantial in academic world today as teachers are expected to take a proactive role to the extent to feel confident and able to carry out broader role that is beyond the traditionally described self-efficacy (Parker, 1998).